THE PREVALANCE OF HEPATITIS C VIRUS ANTIBODIES lN HEMODIALYSIS UNIT - Ercan OK; Hüseyin TÖZ; Nadir YÖNETÇİ and Ali BAŞÇI and Yücel BATUR and Hanefi ÇAVUŞOĞLU (Turkish Journal of Gastroenterology, 2020)
-